Rhetorical Education In America - Glenn, Cheryl (Book collections on Project MUSE., 2004)
A timely collection of essays by prominent scholars in the field-on the past, present, and future of rhetoric instruction. From Isocrates and Aristotle to the present, rhetorical education has consistently been regarded as the linchpin of a participatory democracy, a tool to foster civic action and social responsibility. Yet, questions of who should receive rhetorical education, in what form, and for what purpose, continue to vex teachers and scholars. The essays in this volume converge to explore the purposes, problems, and possibilities of rhetorical education.